Mothers’ Nonstandard Work Schedules, Economic Hardship, and Children’s Outcomes - Afshin Zilanawala; Anika Schenck-Fontaine (Socius)
The authors investigate the moderating role of three dimensions of economic hardship on the relationship between maternal nonstandard work schedules (working evening, nights, or weekends) and children’s behavioral and cognitive outcomes at age five in the United Kingdom. The literature on the relationship between nonstandard work and child development in early childhood has not taken into consideration the potentially important role of families’ economic circumstances. Economic circumstances may reduce or amplify the potential consequences of maternal nonstandard work schedules for young children. Using the Millennium Cohort Study, a nationally representative birth cohort from the United Kingdom, and residualized change models, the authors test associations between children’s cognitive and behavioral outcomes at age five from contemporaneous maternal nonstandard work schedules. Mothers who worked nonstandard schedules had more economic hardship relative to mothers working standard schedules. Nonstandard work schedules were related to higher internalizing behavior scores at age five. The authors examined if observed associations were moderated by income poverty, financial stress, and material hardship, separately, and found that the interaction of nonstandard work with higher levels of financial stress at age five was related to higher internalizing behavior scores. The results highlight a potentially challenging work-family interface in the context of working nonstandard schedules and experiencing economic hardship.